2015
DOI: 10.15252/embr.201541465
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism governing heme synthesis reveals a GATA factor/heme circuit that controls differentiation

Abstract: Metal ion-containing macromolecules have fundamental roles in essentially all biological processes throughout the evolutionary tree. For example, iron-containing heme is a cofactor in enzyme catalysis and electron transfer and an essential hemoglobin constituent. To meet the intense demand for hemoglobin assembly in red blood cells, the cell type-specific factor GATA-1 activates transcription of Alas2, encoding the rate-limiting enzyme in heme biosynthesis, 5-aminolevulinic acid synthase-2 (ALAS-2). Using gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(101 citation statements)
references
References 90 publications
3
97
1
Order By: Relevance
“…The G1E-ER-GATA-1 data was derived from RNA-seq analysis 48 h post-ER-GATA-1 activation (Tanimura et al, 2016) and microarray analysis 24 h after ER-GATA-1 activation (DeVilbiss et al, 2013; Pope and Bresnick, 2013) (Datasets 1 and 2, respectively) (Figure 6A). In R1 cells, −77 loss decreased Gata2 expression, which reduced Gata1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…The G1E-ER-GATA-1 data was derived from RNA-seq analysis 48 h post-ER-GATA-1 activation (Tanimura et al, 2016) and microarray analysis 24 h after ER-GATA-1 activation (DeVilbiss et al, 2013; Pope and Bresnick, 2013) (Datasets 1 and 2, respectively) (Figure 6A). In R1 cells, −77 loss decreased Gata2 expression, which reduced Gata1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…89,90 Further investigation showed that deletion of the int-1-GATA site disrupts the recruitment of the GATA1/TAL1/LMO2/LDB1 complex and fails to fully activate ALAS2 transcription, leading to a failure of developing mature red blood cells and embryonic lethality of mutant males at E12.5. 91,92 A fourth example can be found in the PKLR gene, which encodes pyruvate kinase, an enzyme that catalyzes the final step of glycolysis. Pyruvate kinase deficiency (PKD) is one of the most common causes of hereditary nonspherocytic hemolytic anemia.…”
Section: Gata1 Dysregulation In Human Red Blood Cell Disordersmentioning
confidence: 99%
“…In the context of GATA factors, many prospective enhancers bearing these attributes are either not GATA factor-occupied or can be deleted from a genome with little to no functional consequence (Bresnick et al, 2010; DeVilbiss et al, 2014; Fujiwara et al, 2009; Sanalkumar et al, 2014; Snow et al, 2010; Snow et al, 2011; Tanimura et al, 2015). Previously, we used a multi-parametric prioritization strategy to identify GATA-2-regulated enhancers containing E-box-GATA elements in G1E cells (Hewitt et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Prioritization of GATA-2-occupied E-box-GATA elements with attributes resembling the +9.5 enhancer, and gene editing in G1E mouse erythroid precursor cells revealed sites that regulate their endogenous loci and seemingly similar sites that do not (Hewitt et al, 2015; Tanimura et al, 2015). The functional sites included a conserved intronic enhancer (Samd14-Enh) at the largely unstudied, GATA-2-occupied Samd14 gene (Hewitt et al, 2015).…”
Section: Introductionmentioning
confidence: 99%